CHRONIC MALNUTRITION AND ANTIMALARIAL DRUG RESPONSE IN CHILDREN: A SCOPING REVIEW OF PHARMACOKINETIC ALTERATIONS AND THERAPEUTIC IMPLICATIONS - Priska Ernestina Tenda; Fatmawati Blegur; Yorida F. Maakh; Yohanes M. Abanit; Lely A.V Kapitan; Maria I. M. Indrawati (Journal of World Future Medicine, Health and Nursing, 2026)
Chronic malnutrition remains a significant public health concern in malaria-endemic regions and may substantially influence the pharmacological response to antimalarial therapy in children. Although both malnutrition and malaria have been extensively studied independently, their combined effects on drug pharmacokinetics and treatment outcomes are still not well understood. This gap is largely due to the limited integration of pharmacokinetic, clinical, and nutritional evidence, with only a few studies examining their interaction in shaping antimalarial responses. Therefore, this study aims to systematically map and synthesize existing evidence on how chronic malnutrition affects antimalarial pharmacokinetics and therapeutic outcomes in pediatric populations, while also identifying key research gaps. This scoping review followed PRISMA-ScR guidelines, with a systematic search conducted in PubMed and Scopus that initially identified 1,105 records, of which 56 studies met the inclusion criteria after screening. Data were synthesized narratively to evaluate pharmacokinetic alterations and treatment outcomes, and bibliometric analysis using VOSviewer was performed to map research trends. The findings indicate that chronic malnutrition significantly alters key pharmacokinetic parameters of antimalarial drugs, including absorption, distribution, metabolism, and elimination.